Pengaruh Lingkungan Kerja, Pendidikan dan Prestasi Kerja Terhadap Produktivitas Kerja Karyawan Pada PT. Misaja Mitra Pati - Novitasari, Firsty Candra, Nur Achmad, SE., M.Si (2016)
The purpose of this study was to analyze the influence of the environment, education, and job performance partially or jointly on the productivity of employees at PT. Misaja Partners Pati branch. Quantitative methods used in this study. The primary data of questionnaires distributed directly to employees of PT. Misaja Partners Pati branch. Samples were taken by simple random sampling in order to obtain a sample of 63 respondents. The data analysis technique uses multiple linear regression analysis. Based on the results obtained by t test work environment variables shows that the working environment has a significant impact on employee productivity significance value 0.000 <0.05, employee education variables have a significant influence on employee productivity with significant value 0.038 <0.05, employee performance variables have a significant influence on employee productivity with significant value 0.022 <0.05. Variable working environment, employee education and job performance simultaneous effect on employee productivity with a significance value of 0.000 <0.05. The coefficient of determination (R2) note that the adjusted R-square (R2) of 0.382, meaning variation of the variable changes the employee's productivity can be explained by the work environment, employee education and employee performance of 38.2%. While the rest of 61.8% is explained by other variables outside the model.